Eksistensi Notaris pada Pendirian Perseroan Perorangan dalam Sistem Hukum Positif di Indonesia - Sejati, Mahanany Citraning Putri; Saprudin, Saprudin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The purpose of this research is to analyze the legal certainty of the regulations regarding Individual Companies presented through the Job Creation Law and how the role of Notaries is missing in the process of establishing them. By using normative juridical research, this research is prescriptive, namely to answer legal issues by describing, examining, studying and explaining accurately and analyzing applicable laws and regulations as well as various opinions of legal experts, to obtain answers from issues raised. The research results show that; First, several regulations related to Individual Companies and their establishment do not yet provide legal certainty for the public. This is because the existence of the individual company legal entity has obscured the contractual principles that are applicable to limited liability companies. Thus, the existence of an Individual Company which is only established by 1 (one) person without an agreement is not under the principles that have been adhered to in the establishment of Limited Liability Companies. Second, a Notary does not have the authority to establish an Individual Company because this legal entity can be established with a Statement of Establishment made in Indonesian. However, suppose it is related to other Notary obligations. In that case, the Notary can still have a role as a legal advisor regarding the establishment of a Private Company if requested by the person concerned.